Associations of physical activity in detailed intensity ranges with body composition and physical function. a cross-sectional study among sedentary older adults. - Savikangas, Tiina.; Tirkkonen, Anna.; Alen, Markku.; Rantanen, Taina.; Fielding, Roger A.; Rantalainen, Timo.; Sipilä, Sarianna. (Tufts University. Tisch Library., 2020)
Keywords: Accelerometer, Physical performance, Walking speed, Fat percent, Community-dwelling.; Springer Open.